Uso da cistatina C e de enzimas urinárias para avaliação renal de gestante hipertensa com e sem pré-eclâmpsia e submetida à anestesia subaracnoidea para cesárea - Altamirano, Ivania Guillermina Rodríguez [UNESP] (2014)
Preeclampsia is a multisystemic disease that affects, among other organs, placenta and kidney. Objective: Using multiple biomarkers, assess renal function and tubular integrity after cesarean section in mild preeclamptic patients undergoing subarachnoid anesthesia. Methods: This prospective cohort study examined renal function and tubular integrity of 72 pregnant patients with gestational or chronic hypertension, with and without mild preeclampsia, after cesarean section under subarachnoid anesthesia, having as markers of glomerular filtration rate (GFR) cystatin C and creatinine plasmatic, and of tubular integrity, alkaline phosphatase (AP), γ-glutamyl transpeptidase (γ-GT) and neutrophil gelatinase associated lipocalin (NGAL) urinary, before cesarean section (T1) and 48 h after (T2), distributed among groups: mild preeclampsia (P, case group), n = 27; chronic hypertension and mild preeclampsia superimposed (PH, case group), n = 16; hypertension (H, control group), n = 29. Results: The GFR by cystatin C increased between T1 and T2 for all groups while the GFR by creatinine was significantly decreased in all groups. The values of NGAL increased from T1 to T2 in all groups, and the FA and γ-GT enzymes decreased significantly in T2 of the groups P and H. Conclusions: For the postoperative period of cesarean section of pregnant patients with mild preeclampsia, cystatin C and NGAL were biomarkers not free of bias for the study of renal function. The GFR measured by creatinine showed a slight decrease, consistent with the stress of the perioperative period. There was a reduction of brush border enzymes in hypertensive pregnant patients and in those with pre-eclampsia